An Analysis of Alleged Discrimination by Telkom Group Against Netflix in Internet Service Provision - Kurniawan, Alvin; Setiadi, Edwin; Leonardo, Leonardo; Silalahi, Udin (LOCUS MEDIA PUBLISHING, 2025)
This study analyzes the alleged discriminatory practices by PT Telekomunikasi Indonesia (Persero) Tbk and PT Telekomunikasi Seluler (Telkom Group) against Netflix in the provision of internet access services. The issue arose when Telkom Group blocked access to Netflix in 2016, citing concerns over inappropriate content and consumer protection. However, similar platforms such as HOOQ, Viu, and Iflix were not subjected to the same restrictions, raising concerns about unequal treatment and potential anti-competitive behavior. Using a normative juridical approach combined with statutory, conceptual, and comparative methods, this research examines the case through the lens of Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition and Law No. 36 of 1999 on Telecommunications. The analysis incorporates the principle of non-discrimination and the